2014
DOI: 10.1177/0192623314537723
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Background Changes in Brains of Cynomolgus Monkeys

Abstract: Brain sections from control cynomolgus monkeys (Macaca fascicularis) used in toxicology studies were evaluated retrospectively in order to better understand spontaneous background changes in this species. Hematoxylin and eosin-stained slides from 76 animals (38 males and 38 females) of 9 studies were examined. Eleven animals (9 males and 2 females) were each observed to have 1 to 3 findings within the brain sections examined, for a total of 19 findings. No findings were noted in the spinal cord. The most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…It is established that mononuclear cell infiltrates occasionally occur within the meninges and choroid plexus of the brain and the uveal structures of the eye (Figures 1-3). These have been reported in the literature (Chamanza et al 2010;Sato et al 2012;Butt et al 2014) and recorded by the authors in previous studies. To test whether test article administration results in a quantifiable increase in the number or character of such foci, controls and treated animals were reassessed in a blinded fashion.…”
Section: Background Levels Of Mononuclear Cell Infiltrates Within Consupporting
confidence: 76%
See 1 more Smart Citation
“…It is established that mononuclear cell infiltrates occasionally occur within the meninges and choroid plexus of the brain and the uveal structures of the eye (Figures 1-3). These have been reported in the literature (Chamanza et al 2010;Sato et al 2012;Butt et al 2014) and recorded by the authors in previous studies. To test whether test article administration results in a quantifiable increase in the number or character of such foci, controls and treated animals were reassessed in a blinded fashion.…”
Section: Background Levels Of Mononuclear Cell Infiltrates Within Consupporting
confidence: 76%
“…Some studies were reported to have notable mononuclear cell infiltrates, particularly in the choroid plexus. However, because the presence of low-grade mononuclear infiltrates is known to occur here and in many other sites in NHPs spontaneously (Chamanza et al 2010; Sato et al 2012; Butt et al 2014), this meta-analysis was complimented by reevaluation of the brains from available studies with such findings and a selection of studies without such findings. This was to remove operator variation, to confirm the presence/absence of certain cell types within the infiltrates, and to compare the choroid plexus with the meninges.…”
mentioning
confidence: 99%
“…Inflammatory infiltrates in the brain frequently presented as focal or multifocal perivascular mononuclear cells infiltrations affecting the parenchyma, the meninges, or the choroid plexus. 46 As previously stated, the incidence of this finding in Mauritian macaques was approximately twice that in Chinese- and Vietnamese-origin macaques. The increase in the incidence of mononuclear infiltrates in the brain in Mauritian macaques was determined not to be related to study procedures or dosing since there were no macaques of Mauritian origin that were dosed by the intrathecal route (therefore, results were the same after the few animals dosed by this route were removed), and the distribution of other procedures and dosing routes was comparable between Asian and Mauritian.…”
Section: Discussionmentioning
confidence: 58%
“…Comments: Perivascular infiltrates of mononuclear cells are the most common spontaneous finding in the nervous system of cynomolgus monkeys 6 , 11 . Other cell types such as microglial cells and or oligodendrocytes may be admixed with mononuclear cell infiltrates in the CNS parenchyma and may represent a glial response to the mononuclear cells transiting from the Virchow-Robin space into the parenchyma due to a breach in the blood-brain barrier 279 .…”
Section: Nervous Systemmentioning
confidence: 99%
“…Comments: Scattered aggregates of glial cells are observed as spontaneous findings in the brains of group housed macaques in toxicity studies, and are presumed consequent to minor cerebral trauma incurred during play, aggression or housing transfer. The cell aggregates are mainly composed of microglial cells, oligodendrocytes, and/or astrocytes occasionally admixed with lymphocytes 279 . Numbers of microglial cells have been shown to increase with age in cynomolgus monkey brains 287 .…”
Section: Nervous Systemmentioning
confidence: 99%